New Synthesis Method of Biopolymer Composites Based on Alginate, Carrageenan and ZnONPS for Wound Healing Applications - Mohammed Kassim. Al-Hussainawy; Ali Fahem Getran Khazaali; Makarim A. Mahdi; Waleed K. Abdulsahib; Layth S. Jasim Al-Hayder (Iraqi Journal of Pharmaceutical Sciences)
Abstract